In vitro studies on cellular and humoral chemotaxis in Crohn's disease using the under agarose gel technique. Issue 7 (July 1981) - D'Amelio, R; Rossi, P; Le Moli, S; Ricci, R; Montano, S; Pallone, F
Abstract : The locomotor function of polymorphonuclear cells (cellular chemotaxis) and serum chemotactic activity (humoral chemotaxis) were studied in 51 patients with Crohn's disease using a method of migration under agarose gel. To study cellular chemotaxis patient's polymorphonuclear cells were challenged against normal Zymosan activated serum and humoral chemotaxis was evaluated testing the patient's Zymosan activated serum against normal polymorphonuclear cells. Cellular chemotaxis in the Crohn's disease group was normal (although 30% of the 51 patients had migration values out of the normal range), while humoral chemotaxis was significantly lower in Crohn's disease patients than in the control group. However, the value of humoral chemotaxis in the group of Crohn's disease patients treated with steroids was lower than that of patients not treated, thus accounting for the low mean value observed inthe Crohn's disease-group as a whole. The present results suggest that a defective chemotactic response may occur in some Crohn's disease patients, particularly during steroid treatment. These findings might be related either to a defective generation of complement derived chemotactic factors or to the presence of circulating inhibitors.